PEDAGOGICAL SKILLS OF A TEACHER IN THE PROCESS OF EXCURSIONS - Mirzayeva Manzura Rakhmatdzhanovna (American Journals, 2023)
The article analyzes the formation and development of pedagogical skills in the process of excursions and also reveals the personal qualities of pedagogical activity.
Keywords: pedagogical skills, components, excursion, guide, pedagogical methods, pedagogical process.